Chaotic Behavior of the Forward I-V Characteristic of the Al/a-SiC:H/c-Si(n) Heterojunction - Özer, Mehmet; Hanias, M. P.; Magafas, L.; Stavrinides, S. G.; Papadopoulou, P. (Springer-Verlag Berlin, Heidelberger Platz 3, D-14197 Berlin, Germany, 2013)
In this paper the electrical behavior of the Al/a-SiC:H/c-Si(n) heterojunction for different values of density of gap states (N) in a-SiC:H,is simulated and studied. It is observed that as the density of gap states in a-SiC: H increases from 10(-15) cm(-3) to 10(-18) cm(-3) the I-V characteristics, in the forward bias, present a deviation from the typical I-V of a diode, which is enhanced with the increase of N. For N D 10(-18) cm(-3) the forward I-V characteristic shows strong chaotic vibration that is attributed to the tunneling effect taking place in the junction a-SiC:H/c-Si(n) in the forward bias. With the method of delays correlation and minimum embedding dimension are calculated, while the influence of gap states in strengthening chaos is studied.
Keywords: Physics, Mathematical